2000
DOI: 10.1002/1097-0185(20000701)259:3<327::aid-ar90>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning calorimetry, biochemical, and biomechanical analysis of human skin from individuals with diabetes mellitus

Abstract: The aim of this work was to compare biochemical, two‐dimensional biomechanical and calorimetric parameters of diabetic skin vs. control skin. Skin specimens taken from the palms and backs of the hands of aged persons with non‐insulin‐dependent diabetes mellitus (NIDDM) and of controls (CO) were compared (age range 68–85 years). Only skin specimens from individuals with diabetes mellitus (DM) showed an increased fluorescence specific for the formation of advanced glycation end‐products (AGEs) and the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…A better organization of the collagen helices and/ or homogeneity of fibres in ribosylated samples can be presumed also from the narrower denaturation endotherms, though the change of DT 1/2 was insignificant in meniscus and in young adult cornea (Tables 2-4). Stabilizing effects of glycation were also shown in other DSC studies in tendon [20,303], skin [20,55], lens capsules [56] and bone [25].…”
Section: Discussionsupporting
confidence: 61%
“…A better organization of the collagen helices and/ or homogeneity of fibres in ribosylated samples can be presumed also from the narrower denaturation endotherms, though the change of DT 1/2 was insignificant in meniscus and in young adult cornea (Tables 2-4). Stabilizing effects of glycation were also shown in other DSC studies in tendon [20,303], skin [20,55], lens capsules [56] and bone [25].…”
Section: Discussionsupporting
confidence: 61%
“…DSC thermograms of scleral collagen stabilized by glycerol aldehyde revealed formation of several fractions of collagen, possessing different level of cross-links [26]. Melling et al [24] showed an increase in denaturation temperature in diabetic human skin compared to controls. The changes were consistent with increased collagen stability due to glucose-mediated cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of cross-links induced by glycation on physicochemical properties of collagen were shown in tendon [22,23], skin [22,24], lens capsules [25] and sclera [26]. So far there is no report on effects of glycation on thermal stability of bone collagen.…”
Section: Introductionmentioning
confidence: 99%
“…During denaturation, not only the structure but also the hydration of collagen changes, and thus, not surprisingly, thermal denaturation can lead to remarkable property changes in collagenous tissues, such as the mechanical (Aksan and McGrath, 2003;Bass et al, 2004;Chae et al, 2003;Chao et al, 2001;Chen and Humphrey, 1998;Chen et al, 1997Chen et al, , 1998aDiaz et al, 2001;Harris and Humphrey, 2004;Kondo et al, 2005;Spoerl et al, 2004;Wang et al, 2005;Wells et al, 2004), thermal (Davis et al, 2000;Naseef et al, 1997;Siapi et al, 2005;Tsereteli et al, 1997), and optical (Agah et al, 1996;Bosman, 1993;Essenpreis, 1992;Jun et al, 2003;Lin et al, 1996;Pickering et al, 1994;Ritz et al, 2001a,b;Schwarzmaier et al, 1998;Thomsen and Vijverberg, 1993) properties. However, there are comparatively few studies on skin tissue (Le Lous et al, 1985;Melling et al, 2000;Pierce et al, 2004;Reihsner et al, 2000), despite the skin's dermis being mainly composed of collagen. More experiments are needed to better understand these phenomena and to quantify the variation of skin properties with temperature and the corresponding collagen denaturation, so that these properties can be reliably used in future models.…”
Section: Discussionmentioning
confidence: 99%